Effectiveness Of Restorative Justice In Traffic Accident Case Settlement And Its Implications For The Parties Involved: Research Study At Bintan Police Station - Jul Ilham; Erniyanti Erniyanti; M. Soerya Respationo; Ramlan Ramlan (FKIP, Universitas Palangka Raya, 2024)
Traffic accidents are a severe problem that significantly impacts people's safety and well-being. In Indonesia, the restorative justice approach has been adopted as an alternative to resolving traffic accident cases, which aims to restore the relationship between the perpetrator and the victim and reduce the burden on the criminal justice system. This study focuses on the effectiveness of the implementation of restorative justice by the Bintan Subregional Police in resolving traffic accident cases in Batam City, as well as its implications for the parties involved. This study aims to analyze how the application of restorative justice can affect the settlement of traffic accident cases, assess the effectiveness of this approach, and identify relevant obstacles and solutions to optimize its implementation. The research method used is qualitative, collecting data through in-depth interviews, observations, and document analysis. The research respondents comprised police officers, victims, perpetrators, and community leaders involved in the mediation process. The study results show that implementing restorative justice by the Bintan Subregional Police has excellent potential to create a fairer and more satisfactory settlement for all parties involved. However, its effectiveness is still hampered by limited resources and training for the police, lack of public understanding, and suboptimal coordination between institutions. The proposed solutions include increasing training programs for police officers, drafting more detailed regulations, and intensifying socialization to the public about the benefits and processes of restorative justice. The study suggests that police forces increase training and resources, communities are more active in supporting this approach, and governments develop regulations that support and improve coordination between agencies. By overcoming these obstacles, the application of restorative justice in resolving traffic accident cases can be more effective and provide more significant benefits to the community, as well as increase trust in the criminal justice system in Indonesia.